ANALISIS SISTEM PENGENDALIAN INTERNAL TERHADAP SISTEM AKUNTANSI PENGGAJIAN - Rachmawati, Ika; Mulyati, Awin; Mulyati, Diana (Jurnal Dinamika Administrasi Bisnis, 2015)
One of the important activities conducted by each company is employee payroll. This study aims to determine the internal controls in the payroll system which has been implemented by the company.Â The data analysis technique used is descriptive qualitative analysis technique to describe the internal control system implemented in the company's payroll.The results showed the company has not yet implemented the control system so well that may arise fraud management employee salaries. Implications arising fraud in the calculation of working time of employees; the employee time data manipulation; and errors in the payment of salaries of employees.Improvements that can be made form of accounting and finance division and division personnel; implementing authority systems and procedures in both the recording. Another improvement is the presence of accounting functions which authorize the salaries of employees before paid. Keywords: Systems, Payroll, Internal Control